STRATEGI PENINGKATAN KUALITAS PELAYANAN SIM CAK BHABIN DI POLRESTABES KOTA SURABAYA - Susi Ratnawati; Tri Prasetijowati; Fionita Eka Putri (P3M STISIPOL Dharma Wacana Metro, 2023)
Making and extending a driver's license is one of the common needs of the Indonesian people, especially motorists. Based on this, the Polrestabes created a Mobile SIM innovation called